Comparison of the effects of deferasirox film-coated tablets (Jadenu®) and deferasirox dispersible tablets (Exjade®) in patients with beta thalassemia major: a preliminary report of the effects on the satisfaction, convenience, cardiac/liver MRI T2*, serum ferritin level, and biochemical profiles - Mobinikhaledi, Mahya; Falahati, Vahid; Tajerian, Amin; Hashiani, Amir Almasi; Ghaffari, Kazem; Ghasemi, Ali (Frontiers in Pharmacology, 2024)
Background: Defrasirox (DFX) is a once-daily oral iron chelator with proven dose-dependent efficacy in patients with thalassemia major. The reason for switching from DFX Dispersible Tablets (Exjade®) to DFX Film-Coated Tablets (Jadenu®) was intolerance. Many also reported that Deferasirox® did not taste good. In this study, we compared the effect of Jadenu® and Exjade® on the satisfaction, convenience, cardiac/liver MRI T2*, serum ferritin level, and biochemical profiles in patients with thalassemia major.Method: Sixty-two patients with thalassemia over 2 years of age with iron overload indicated by chelation therapy were randomly divided into two groups. The first group (n = 32) is treated with Exjade® and the second group (n = 30) is treated with Jadenu®. Lab investigations included alkaline phosphatase (ALK), alanine transferase (ALT), aspartate transferase (AST) and serum ferritin level,. Cardiac/liver MRI T2* and satisfaction, convenience, before and one year after starting therapy, were also assessed.The study found that 53.3% of Jadenu® patients were satisfied with the taste of the medication compared to only 12.5% of Exjade® patients, which was statistically significant (P=0.001). Additionally, 40% of Jadenu® patients were satisfied with the way of taking the medication compared to 28.1% of Exjade® patients, and again, the difference was statistically significant (P=0.047). Comparison of cardiac MRI T2* level between the two studied groups showed that there is no significant difference between the two groups (P=0.851).Conclusions: Jadenu® offers patients an improved formulation that can be taken on an empty stomach, has a better taste, and minimal gastrointestinal tolerability concerns. Overall, patient satisfaction is higher with Jadenu®, which may improve adherence and reduce the frequency and severity of complications associated with iron overload. This, in turn, may help mitigate cardiovascular and hepatic complications from iron overload in the long term.